Postponing maternity in Ireland - Cathal O'Donoghue; David Meredith; Eamon O'Shea (Institute for the Study of Labor (IZA), 2009)
As in many other developed countries, Ireland in recent decades has experienced a postponement of maternity. In this paper we consider the main trends in this phenomenon, considering changes in first and later births separately. We adapt the theoretical model due to Walker (1995) to incorporate a declining marginal return to experience to provide a human capital/career planning explanation for this postponement. We estimate a hazard model based upon the 1994 Living in Ireland Survey to empirically test this model. The career-planning hypothesis was found to hold. However an assumption about perfect capital markets failed indicating the impact of an income effect on the timing of maternity. The model also identified the importance of cohort differences in the timing of marriage in explaining much of the inter-cohort specific differences in the timing of maternity.
urn:nbn:de:101:1-2009061570
Keywords: J13; 330; Labour markets; fertility; Mütter; Fruchtbarkeit; Frauenerwerbstätigkeit; Karriereplanung; Schätzung; Irland